La felicidad laboral factor clave en las empresas para retener el talento humano (2019)
Happiness at work is the challenge faced by companies, as a strategy to retain staff, understand the concept of happiness and take it to work is the constant task to implement strategies that lead to generate happiness in each of the workers. Defining happiness has been a study and concern since ancient times, and based on the literature review and research carried out, happiness will be addressed as one of the important factors in retaining and maintaining human talent, a vital resource of any company. The flight of personnel is a constant risk due to globalization and competitiveness, today we talk about the management of people, to have positive results that contribute to making companies sustainable.